2018
DOI: 10.1016/j.engstruct.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of reinforced concrete frame with masonry infill wall subjected to vertical load

Abstract: The effectiveness of masonry infill wall on behavior of a Reinforced Concrete (RC) frame subjected to a column failure is studied experimentally. For this reason, one full scale RC frame designed according to Eurocode is statically tested to investigate the behavior of the frame with and without masonry infill wall. The obtained results show that infill wall can significantly increase the load carrying capacity of RC frame and thus serve as an important robustness reserve in the case of unpredictable extreme e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Although the packed wall is a nonstructural part, it still has an important influence on the mechanical mechanism and seismic performance of the structural system under the action of earthquake [6][7][8]. In addition, related studies show that infill wall can significantly increase the load-carrying capacity of the RC frame and thus serve as an important robustness reserve in the case of unpredictable extreme events [9]. Therefore, while paying attention to the study of new structures and complex structures, it is undoubtedly of great engineering practical significance to reexamine and study the seismic performance of masonry-infilled frame structure which is the most widely used in buildings, and fully understand the impact of infill walls on RC frame structure, and ensure the seismic safety of this kind of structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although the packed wall is a nonstructural part, it still has an important influence on the mechanical mechanism and seismic performance of the structural system under the action of earthquake [6][7][8]. In addition, related studies show that infill wall can significantly increase the load-carrying capacity of the RC frame and thus serve as an important robustness reserve in the case of unpredictable extreme events [9]. Therefore, while paying attention to the study of new structures and complex structures, it is undoubtedly of great engineering practical significance to reexamine and study the seismic performance of masonry-infilled frame structure which is the most widely used in buildings, and fully understand the impact of infill walls on RC frame structure, and ensure the seismic safety of this kind of structure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, infill walls could help to reduce the shear deformation of the beam-column joints. Baghi et al [19] demonstrated that masonry walls can increase the energy dissipation capacity and the toughness of the infilled frame 270% higher than bare frame. Brodsky and Yankelevsky [20] experimentally assessed the contribution of infill masonry walls to resist progressive collapse.…”
Section: Introductionmentioning
confidence: 99%
“…is interaction may or may not be beneficial to the performance of the structure [3,4]. For instance, the existence of masonry infill in an RC frame can increase the strength, stiffness, and lateral capacity of the building [5][6][7].…”
Section: Introductionmentioning
confidence: 99%